Causes of missed nursing care: qualitative responses to a survey of Australian nurses. (1st October 2016) - Henderson, Julie; Willis, Eileen; Blackman, Ian; Toffoli, Luisa; Verrall, Claire
ABSTRACT: There is a growing nursing literature that views missed nursing care as an inevitable consequence of work intensification associated with the rationing of the human and material resources required to deliver care. A modified MISSCARE survey was administered to 4431 nurses and midwives in New South Wales in November 2014. This paper reports on 947 responses to an open question contained in the survey which asked respondents 'Is there anything else you would like to tell us about missed care?' Responses were analysed using qualitative content analysis and focused upon both the causes and impact of missed care. Analysis identified two major causes of missed care: the impact of work intensification and staffing issues. Participants associated work intensification with patient acuity and cost containment, while the staffing issues identified included: undermining prescribed staffing ratios; skill mix; changing workloads across shifts; and poor support from other staff. Respondents identified insufficient resources, albeit staffing or other resources, to meet patient care needs reflecting findings in similar studies. Missed or delayed nursing care in this context is associated with resource issues leading nurses to ration the care they can provide. While work intensification is not a new phenomenon, its increasing use in the public hospital sector across a number of OECD countries has become a major consequence of new public management (NPM) strategies aimed at cost containment.